Angiography (IntechOpen, 2023)
Atherosclerotic cardiovascular disease is still the most common cause of death among adults. Its prevalence is increasing in developing countries and despite all advances in both diagnostic tools and treatment modalities, it is still very common in the developed world. Obesity, diabetes mellitus, hypercholesterolemia, and overuse of dietary salt play a pivotal role in increased cardiovascular morbidity and mortality worldwide. Current clinical efforts are mainly focused on the diagnosis and treatment of myocardial infarction. In this book we provide epidemiological data on myocardial infarction and atherosclerotic cardiovascular disease, current diagnostic biochemical tests, and management strategies. A specific patient group, children, experiencing myocardial infarction is also addressed. Current advancements in the management of myocardial infarction have decreased the morbidity and mortality from atherosclerotic cardiovascular disease and especially myocardial infarction; however, further progress can be achieved by the prevention of atherosclerotic processes by focusing on the early stages of the disease.